Pelatihan Komposisi untuk Peningkatan Desain Motif Bahan dan Desain Fashion bagi Pengrajin Shibori dan Ecoprint - Christian Nindyaputra Octarino; Patricia Pahlevi Noviandri (Universitas Katolik Soegijapranata, 2020)
For most people, fashion and lifestyle are two things that cannot be separated. Dressing is not just to cover the body, but it can symbolize someone's personality and identity. Therefore, fashion manufacturers competing to bring innovations to their products so that they can attract more people. One of the innovations in the field of fashion is ecoprint and shibori, which emphasizes the use of natural dyes in the manufacturing process. With the phenomenon of environmental pollution, this technique becomes more popular because it promises an environmentally friendly on its process. Not only from processing techniques, innovation also needs to be done on the design of the product. Design remains one of the main considerations of consumers in buying a product, including fashion products. This study was conducted during the Workshop of Design Composition for motif and fashion Improvement, initiated by Faculty of Architecture and Design UKDW collaborated with Paroki Keluarga Kudus Banteng dan PEJ GKJ Pakem Yogyakarta. This workshop focuses on the creativity of artisans in finding interesting compositions used in shibori and ecoprint techniques. Furthermore, the workshop method will also be used to find designs for fashion products that are attractive and suitable for the market in the present. The purpose of this study was to determine the effectiveness of the workshop method used for the responses and achievements of the participants.